Controllable Synthesis of NiCo LDH Nanosheets for Fabrication of High‐Performance Supercapacitor Electrodes. Issue 5 (7th February 2017) - Wang, Xueqin; Li, Xiumin; Du, Xiao; Ma, Xuli; Hao, Xiaogang; Xue, Chunfeng; Zhu, Hongye; Li, Shasha
Abstract: A unipolar pulse electrodeposition method was employed to controllably synthesize nanosheet type NiCo LDH. The effect of concentration rate of Ni(NO3 )2 /Co(NO3 )2 preparation solution on crystalline structure, morphology and supercapacitive performance was investigated systematically. Experimental found that the morphology and composition of NiCo LDH was highly depend on the Ni 2+ /Co 2+ molar ratios of preparation solution; and the obtained Ni0.76 Co0.24 LDH materials showed small nanosheet size and uniform distribution on carbon fiber electrode. Ni0.76 Co0.24 LDH electrode was evaluated for supercapacitor application, which revealed a high specific capacitances of 2189.8 and 1908.8 F g −1 at the current density of 1 and 30 A g −1 respectively and a good cycle stability, retaining 70.3 % of the initial capacitance after 20000 charge and discharge cycles at 50 A g −1 . Moreover, the Ni0.76 Co0.24 LDH electrode exhibits a high energy density of 76 Wh Kg −1 at a power density of 250 W Kg −1 and a high power density of 7500 W Kg −1 at energy density of 66 Wh Kg −1 . The as‐prepared Ni0.76 Co0.24 LDH as positive electrode for asymmetric supercapacitor exhibits excellent energy density of 4.1 Wh Kg ‐1 at a power density of 4000 W Kg ‐1 Abstract :